An Earth-Sized Planet in the Habitable Zone of a Cool Star. - Quintana, Elisa; Barclay, Thomas; Raymond, Sean; Rowe, Jason; Bolmont, Emeline; Caldwell, Douglas; Howell, Steve; Kane, Stephen; Huber, Daniel; Crepp, Justin; Lissauer, Jack; Ciardi, David; et al. (Science, 2014)
The quest for Earth-like planets is a major focus of current exoplanet research. Although planets that are Earth-sized and smaller have been detected, these planets reside in orbits that are too close to their host star to allow liquid water on their surfaces. We present the detection of Kepler-186f, a 1.11 ± 0.14 Earth-radius planet that is the outermost of five planets, all roughly Earth-sized, that transit a 0.47 ± 0.05 solar-radius star. The intensity and spectrum of the star's radiation place Kepler-186f in the stellar habitable zone, implying that if Kepler-186f has an Earth-like atmosphere and water at its surface, then some of this water is likely to be in liquid form.
189 citations (Crossref) [2023-10-31] Place: Copyright (C) 2014 by the American Association for the Advancement of Science
Keywords: Earth; Earth (Planet); Exobiology; Extraterrestrial Environment; Planets; Stars; Celestial; Water; astrobiology; astronomy; atmosphere; cosmic radiation; dept.phy; habitat use; microclimate; priority journal; review; solar system; surface property; water

Validation of small Kepler transiting planet candidates in or near the habitable zone - Torres, Guillermo; Kane, Stephen R.; Rowe, Jason F.; Batalha, Natalie M.; Henze, Christopher E.; Ciardi, David R.; Barclay, Thomas; Borucki, William J.; Buchhave, Lars A.; Crepp, Justin R.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
A main goal of NASA's Kepler Mission is to establish the frequency of potentially habitable Earth-size planets (). Relatively few such candidates identified by the mission can be confirmed to be rocky via dynamical measurement of their mass. Here we report an effort to validate 18 of them statistically using the BLENDER technique, by showing that the likelihood they are true planets is far greater than that of a false positive. Our analysis incorporates follow-up observations including high-resolution optical and near-infrared spectroscopy, high-resolution imaging, and information from the analysis of the flux centroids of the Kepler observations themselves. Although many of these candidates have been previously validated by others, the confidence levels reported typically ignore the possibility that the planet may transit a star different from the target along the same line of sight. If that were the case, a planet that appears small enough to be rocky may actually be considerably larger and therefore less interesting from the point of view of habitability. We take this into consideration here and are able to validate 15 of our candidates at a 99.73% (3σ) significance level or higher, and the other three at a slightly lower confidence. We characterize the GKM host stars using available ground-based observations and provide updated parameters for the planets, with sizes between 0.8 and 2.9 R ⊕. Seven of them (KOI-0438.02, 0463.01, 2418.01, 2626.01, 3282.01, 4036.01, and 5856.01) have a better than 50% chance of being smaller than 2 R ⊕ and being in the habitable zone of their host stars. © 2017. The American Astronomical Society. All rights reserved..
20 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-258-082-978-883, pop00029 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; peer-reviewed; planetary systems; stars: individual (KOI-0172.02 = Kepler-69c ...); techniques: photometric

Validation of Twelve Small Kepler Transiting Planets in the Habitable Zone - Caldwell, Douglas A.; Torres, Guillermo; Kipping, David M.; Ballard, Sarah; Batalha, Natalie; Borucki, William J.; Bryson, Steve; Ciardi, David R.; Crepp, Justin R.; Everett, Mark; Fressin, Francois; Henze, Christopher; et al. (2015)
We report on the work to validate twelve candidate-transiting planets from Kepler with orbital periods ranging from 34 to 207 days initially identified in the pipeline search of three years of Kepler data from quarters 1 to 12. The candidates were selected based on pipeline Data Validation models indicating that they are small and potentially in the habitable zone (HZ) of their parent stars. As their expected Doppler signals are too small for a direct measure of their masses, we verify their planetary nature by validating them statistically using the BLENDER technique. BLENDER simulates large numbers of false-positive scenarios and compares the resulting light curves with the Kepler photometry, taking into account additional information from the analysis of Kepler flux centroids and new follow-up observations, including high-resolution optical and NIR spectroscopy, adaptive optics imaging, and speckle imaging. For eleven of the candidates we show that the likelihood they are true planets is far greater than that of a false positive, to a 99.73% confidence level. For the twelfth candidate, the planet confidence level is about 99.2%. Using improved stellar parameters for the host stars, we derive planetary radii ranging from 1.12 to 2.73 R⊕. All twelve objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of the candidates that have been previously validated by others, our study doubles the number of known potentially rocky planets in the HZ.
Conference Name: American Astronomical Society Meeting Abstracts #225 ADS Bibcode: 2015AAS...22543802C
Keywords: dept.phy

Validation of 12 small kepler transiting planets in the habitable zone - Torres, Guillermo; Kipping, David M; Fressin, Francois; Caldwell, Douglas A; Twicken, Joseph D; Ballard, Sarah; Batalha, Natalie M; Bryson, Stephen T; Ciardi, David R; Henze, Christopher E; Howell, Steve B; Isaacson, Howard; et al. (The Astrophysical Journal, 2015)
We present an investigation of 12 candidate transiting planets from Kepler with orbital periods ranging from 34 to 207 days, selected from initial indications that they are small and potentially in the habitable zone (HZ) of their parent stars. Few of these objects are known. The expected Doppler signals are too small to confirm them by demonstrating that their masses are in the planetary regime. Here we verify their planetary nature by validating them statistically using the BLENDER technique, which simulates large numbers of false positives and compares the resulting light curves with the Kepler photometry. This analysis was supplemented with new follow-up observations (high-resolution optical and near-infrared spectroscopy, adaptive optics imaging, and speckle interferometry), as well as an analysis of the flux centroids. For 11 of them (KOI-0571.05, 1422.04, 1422.05, 2529.02, 3255.01, 3284.01, 4005.01, 4087.01, 4622.01, 4742.01, and 4745.01) we show that the likelihood they are true planets is far greater than that of a false positive, to a confidence level of 99.73% (3σ) or higher. For KOI-4427.01 the confidence level is about 99.2% (2.6σ). With our accurate characterization of the GKM host stars, the derived planetary radii range from 1.1 to 2.7 R ⊕. All 12 objects are confirmed to be in the HZ, and nine are small enough to be rocky. Excluding three of them that have been previously validated by others, our study doubles the number of known rocky planets in the HZ. KOI-3284.01 (Kepler-438b) and KOI-4742.01 (Kepler-442b) are the planets most similar to the Earth discovered to date when considering their size and incident flux jointly. © 2015. The American Astronomical Society. All rights reserved..
94 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-512-292-095-617 tex.type: [object Object]
Keywords: dept.phy; methods: statistical; planetary systems; stars: individual (KOI-3284 (Kepler-438); KOI-4742 (Kepler-442)); techniques: photometric

A sub-Mercury-sized exoplanet. - Barclay, Thomas; Rowe, Jason; Lissauer, Jack; Huber, Daniel; Fressin, Francois; Howell, Steve; Bryson, Stephen; Chaplin, William; Desert, Jean-Michel; Lopez, Eric; Marcy, Geoffrey; Mullally, Fergal; et al. (Nature, 2013)
Since the discovery of the first exoplanets, it has been known that other planetary systems can look quite unlike our own. Until fairly recently, we have been able to probe only the upper range of the planet size distribution, and, since last year, to detect planets that are the size of Earth or somewhat smaller. Hitherto, no planets have been found that are smaller than those we see in the Solar System. Here we report a planet significantly smaller than Mercury. This tiny planet is the innermost of three that orbit the Sun-like host star, which we have designated Kepler-37. Owing to its extremely small size, similar to that of the Moon, and highly irradiated surface, the planet, Kepler-37b, is probably rocky with no atmosphere or water, similar to Mercury. © 2013 Macmillan Publishers Limited. All rights reserved.
161 citations (Crossref) [2023-10-31] Place: (C) 2013 Nature Publishing Group
Keywords: Earth; article; astronomy; atmosphere; dept.phy; irradiance; irradiation; moon; orbit determination; planetary surface; priority journal; size structure; solar system; sun; water

Transit timing observations from kepler: III. confirmation of 4 multiple planet systems by a fourier-domain study of anti-correlated transit timing variations - Steffen, Jason H.; Fabrycky, Daniel C.; Ford, Eric B.; Carter, Joshua A.; Désert, Jean-Michel; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Rowe, Jason F.; Ragozzine, Darin; Welsh, William F.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to confirm the planetary nature of objects in systems with multiple transiting exoplanet candidates. This method involves a Fourier-domain analysis of the deviations in the transit times from a constant period that result from dynamical interactions within the system. The combination of observed anticorrelations in the transit times and mass constraints from dynamical stability allow us to claim the discovery of four planetary systems, Kepler-25, Kepler-26, Kepler-27 and Kepler-28, containing eight planets and one additional planet candidate. © 2012 Fermi Research Alliance LLC, Contractor for the U.S. Dept of Energy Monthly Notices of the Royal Astronomical Society © 2012 RAS.
121 citations (Crossref) [2023-10-31] Citation Key Alias: pop00008 tex.type: [object Object]
Keywords: Celestial mechanics; Methods: data analysis; Stars: individual: KIC 4349452; Stars: individual: KIC 5792202; Stars: individual: KIC 6949607; Stars: individual: KIC 9757613; dept.phy; peer-reviewed

Transit timing observations from kepler. II. confirmation of two multiplanet systems via a non-parametric correlation analysis - Ford, Eric B.; Fabrycky, Daniel C.; Steffen, Jason H.; Carter, Joshua A.; Fressin, Francois; Holman, Matthew J.; Lissauer, Jack J.; Moorhead, Althea V.; Morehead, Robert C.; Ragozzine, Darin; Rowe, Jason F.; Welsh, William F.; et al. (The Astrophysical Journal, 2012)
We present a new method for confirming transiting planets based on the combination of transit timing variations (TTVs) and dynamical stability. Correlated TTVs provide evidence that the pair of bodies is in the same physical system. Orbital stability provides upper limits for the masses of the transiting companions that are in the planetary regime. This paper describes a non-parametric technique for quantifying the statistical significance of TTVs based on the correlation of two TTV data sets. We apply this method to an analysis of the TTVs of two stars with multiple transiting planet candidates identified by Kepler. We confirm four transiting planets in two multiple-planet systems based on their TTVs and the constraints imposed by dynamical stability. An additional three candidates in these same systems are not confirmed as planets, but are likely to be validated as real planets once further observations and analyses are possible. If all were confirmed, these systems would be near 4:6:9 and 2:4:6:9 period commensurabilities. Our results demonstrate that TTVs provide a powerful tool for confirming transiting planets, including low-mass planets and planets around faint stars for which Doppler follow-up is not practical with existing facilities. Continued Kepler observations will dramatically improve the constraints on the planet masses and orbits and provide sensitivity for detecting additional non-transiting planets. If Kepler observations were extended to eight years, then a similar analysis could likely confirm systems with multiple closely spaced, small transiting planets in or near the habitable zone of solar-type stars. © 2012. The American Astronomical Society. All rights reserved.
73 citations (Crossref) [2023-10-31] Citation Key Alias: pop00013 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; planets and satellites: dynamical evolution and stability; stars: individual (KIC 3231341; 11512246; KOI 168; 1102; Kepler-23; Kepler-24); techniques: miscellaneous

Kepler Planet-Detection Mission: Introduction and First Results. - Borucki, William; Koch, David; Basri, Gibor; Batalha, Natalie; Brown, Timothy; Caldwell, Douglas; Caldwell, John; Christensen-Dalsgaard, Jorgen; Cochran, William; DeVore, Edna; Dunham, Edward; Dupree, Andrea; et al. (Science, 2010)
The Kepler mission was designed to determine the frequency of Earth-sized planets in and near the habitable zone of Sun-like stars. The habitable zone is the region where planetary temperatures are suitable for water to exist on a planet's surface. During the first 6 weeks of observations, Kepler monitored 156,000 stars, and five new exoplanets with sizes between 0.37 and 1.6 Jupiter radii and orbital periods from 3.2 to 4.9 days were discovered. The density of the Neptune-sized Kepler-4b is similar to that of Neptune and GJ 436b, even though the irradiation level is 800,000 times higher. Kepler-7b is one of the lowest-density planets (∼0.17 gram per cubic centimeter) yet detected. Kepler-5b, -6b, and -8b confirm the existence of planets with densities lower than those predicted for gas giant planets.
2612 citations (Crossref) [2023-10-31] Place: Copyright (C) 2010 by the American Association for the Advancement of Science
Keywords: Jupiter; article; astronomy; astrophysics; density; dept.phy; gas; irradiation; planetary atmosphere; planetary surface; priority journal; spacecraft; sun; temperature; water

Characteristics of kepler planetary candidates based on the first data set - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Boss, Alan P.; Brown, Timothy M.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Dupree, Andrea K.; et al. (The Astrophysical Journal, 2011)
In the spring of 2009, the Kepler Mission commenced high-precision photometry on nearly 156,000 stars to determine the frequency and characteristics of small exoplanets, conduct a guest observer program, and obtain asteroseismic data on a wide variety of stars. On 2010 June 15, the Kepler Mission released most of the data from the first quarter of observations. At the time of this data release, 705 stars from this first data set have exoplanet candidates with sizes from as small as that of Earth to larger than that of Jupiter. Here we give the identity and characteristics of 305 released stars with planetary candidates. Data for the remaining 400 stars with planetary candidates will be released in 2011 February. More than half the candidates on the released list have radii less than half that of Jupiter. Five candidates are present in and near the habitable zone; two near super-Earth size, and three bracketing the size of Jupiter. The released stars also include five possible multi-planet systems. One of these has two Neptune-size (2.3 and 2.5 Earth radius) candidates with near-resonant periods. © 2011. The American Astronomical Society.
282 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: Planets and satellites: detection; Surveys; dept.phy

Characteristics of planetary candidates observed by Kepler II : Analysis of the first four months of data - Borucki, William J.; Koch, David G.; Basri, Gibor; Batalha, Natalie M.; Brown, Timothy M.; Bryson, Stephen T.; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Dunham, Edward W.; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2011)
On 2011 February 1 the Kepler mission released data for 156,453 stars observed from the beginning of the science observations on 2009 May 2 through September 16. There are 1235 planetary candidates with transit-like signatures detected in this period. These are associated with 997 host stars. Distributions of the characteristics of the planetary candidates are separated into five class sizes: 68 candidates of approximately Earth-size (Rp < 1.25 R⊕), 288 super-Earth-size (1.25 R⊕ ≤ R p < 2 R⊕), 662 Neptune-size (2 R ⊕ ≤ Rp < 6 R⊕), 165 Jupiter-size (6 R⊕ ≤ Rp < 15 R ⊕), and 19 up to twice the size of Jupiter (15 R ⊕ ≤ Rp < 22 R⊕). In the temperature range appropriate for the habitable zone, 54 candidates are found with sizes ranging from Earth-size to larger than that of Jupiter. Six are less than twice the size of the Earth. Over 74% of the planetary candidates are smaller than Neptune. The observed number versus size distribution of planetary candidates increases to a peak at two to three times the Earth-size and then declines inversely proportional to the area of the candidate. Our current best estimates of the intrinsic frequencies of planetary candidates, after correcting for geometric and sensitivity biases, are 5% for Earth-size candidates, 8% for super-Earth-size candidates, 18% for Neptune-size candidates, 2% for Jupiter-size candidates, and 0.1% for very large candidates; a total of 0.34 candidates per star. Multi-candidate, transiting systems are frequent; 17% of the host stars have multi-candidate systems, and 34% of all the candidates are part of multi-candidate systems. © 2011. The American Astronomical Society. All rights reserved.
799 citations (Crossref) [2023-10-31] Citation Key Alias: pop00002 tex.type: [object Object]
Keywords: dept.phy; planetary systems; planets and satellites: detection; stars: statistics; surveys

Kepler-22b: A 2.4 Earth-radius Planet in the Habitable Zone of a Sun-like Star - Borucki, William J.; Koch, David G.; Batalha, Natalie M.; Bryson, Stephen T.; Rowe, Jason F.; Fressin, Francois; Torres, Guillermo; Caldwell, Douglas A.; Christensen-Dalsgaard, Jørgen; Cochran, William D.; DeVore, Edna; Gautier, Thomas N.; et al. (The Astrophysical Journal, 2012)
A search of the time-series photometry from NASA's Kepler spacecraft reveals a transiting planet candidate orbiting the 11th magnitude G5 dwarf KIC 10593626 with a period of 290 days. The characteristics of the host star are well constrained by high-resolution spectroscopy combined with an asteroseismic analysis of the Kepler photometry, leading to an estimated mass and radius of 0.970 0.060 M and 0.979 0.020 R. The depth of 492 10 ppm for the three observed transits yields a radius of 2.38 0.13 Re for the planet. The system passes a battery of tests for false positives, including reconnaissance spectroscopy, high-resolution imaging, and centroid motion. A full BLENDER analysis provides further validation of the planet interpretation by showing that contamination of the target by an eclipsing system would rarely mimic the observed shape of the transits. The final validation of the planet is provided by 16 radial velocities (RVs) obtained with the High Resolution Echelle Spectrometer on Keck I over a one-year span. Although the velocities do not lead to a reliable orbit and mass determination, they are able to constrain the mass to a 3σ upper limit of 124 M ⊕, safely in the regime of planetary masses, thus earning the designation Kepler-22b. The radiative equilibrium temperature is 262 K for a planet in Kepler-22b's orbit. Although there is no evidence that Kepler-22b is a rocky planet, it is the first confirmed planet with a measured radius to orbit in the habitable zone of any star other than the Sun. © 2012. The American Astronomical Society. All rights reserved.
186 citations (Crossref) [2023-10-31] Citation Key Alias: pop00003 tex.type: [object Object]
Keywords: dept.phy; planetary systems; stars: fundamental parameters; stars: individual (Kepler-22; KIC 10593626)

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-363-095-757-409, pop00014 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830; TOI-175); techniques: photometric